Establishment of organoids using residual samples from saline flushes during endoscopic ultrasound-guided fine-needle aspiration in patients with pancreatic cancer - Ikezawa, Kenji; Ekawa, Tomoya; Hasegawa, Shinichiro; Kai, Yugo; Takada, Ryoji; Yamai, Takuo; Fukutake, Nobuyasu; Ogawa, Hisataka; Akazawa, Takashi; Mizote, Yu; Tatsumi, Kumiko; Nagata, Shigenori; Asukai, Kei; Takahashi, Hidenori; Ohkawa, Kazuyoshi; Tahara, Hideaki (Endoscopy International Open, 2022)
Background and study aims In patients with pancreatic cancer (PC), patient-derived organoid cultures can be useful tools for personalized drug selection and preclinical evaluation of novel therapies. To establish a less invasive method of creating organoids from a patient’s tumor, we examined whether PC organoids can be established using residual samples from saline flushes (RSSFs) during endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA).Methods Five patients with PC who underwent EUS-FNA were enrolled in a prospective study conducted at our institution. RSSFs obtained during EUS-FNA procedures were collected. An organoid culture was considered as established when ≥ 5 passages were successful. Organoid-derived xenografts were created using established organoids.Results EUS-FNA was performed using a 22- or 25-gauge lancet needle without complications. Patient-derived organoids were successfully established in four patients (80.0 %) with the complete medium and medium for the selection of KRAS mutants. Organoid-derived xenografts were successfully created and histologically similar to EUS-FNA samples. Conclusions Patient-derived PC organoids were successfully established using EUS-FNA RSSFs, which are produced as a byproduct of standard manipulations, but are usually not used for diagnosis. This method can be applied to all patients with PC, without additional invasive procedures, and can contribute to the development of personalized medicine and molecular research.